MiR‐34a deficiency accelerates medulloblastoma formation in vivo. Issue 10 (25th November 2014) - Thor, Theresa; Künkele, Annette; Pajtler, Kristian W.; Wefers, Annika K.; Stephan, Harald; Mestdagh, Pieter; Heukamp, Lukas; Hartmann, Wolfgang; Vandesompele, Jo; Sadowski, Natalie; Becker, Lore; Garrett, Lillian; et al.
<x xml:space="preserve">Abstract</x> Previous studies have evaluated the role of miRNAs in cancer initiation and progression. MiR‐34a was found to be downregulated in several tumors, including medulloblastomas. Here we employed targeted transgenesis to analyze the function of miR‐34a in vivo. We generated mice with a constitutive deletion of the miR‐34a gene. These mice were devoid of mir‐34a expression in all analyzed tissues, but were viable and fertile. A comprehensive standardized phenotypic analysis including more than 300 single parameters revealed no apparent phenotype. Analysis of miR‐34a expression in human medulloblastomas and medulloblastoma cell lines revealed significantly lower levels than in normal human cerebellum. Re‐expression of miR‐34a in human medulloblastoma cells reduced cell viability and proliferation, induced apoptosis and downregulated the miR‐34a target genes, MYCN and SIRT1. Activation of the Shh pathway by targeting SmoA1 transgene overexpression causes medulloblastoma in mice, which is dependent on the presence and upregulation of Mycn. Analysis of miR‐34a in medulloblastomas derived from ND2:SmoA1(tg) mice revealed significant suppression of miR‐34a compared to normal cerebellum. Tumor incidence was significantly increased and tumor formation was significantly accelerated in mice transgenic for SmoA1 and lacking miR‐34a. Interestingly, Mycn and Sirt1 were strongly expressed in medulloblastomas derived from these mice. We here demonstrate that miR‐34a is dispensable for normal development, but that its loss accelerates medulloblastomagenesis. Strategies aiming to re‐express miR‐34a in tumors could, therefore, represent an efficient therapeutic option.